THE IMPLEMENTATION OF HUMAN RIGHTS IN LABOUR AND HUMAN TRAFFICKING LAW ON WOMEN - Sulistyowati Sulistyowati (International Journal of Law Reconstruction, 2021)
This study aims to analyze implementation of human rights in economic field and role of the Government, Educational Institutions and Non-Governmental Organizations in the prevention and control of trafficking in women. How to achieve the goal, is done by empirical studies and documentation studies, to obtain primary and secondary data. This research is descriptive analytical. The approach method used is empirical juridical. Data analysis was carried out in a qualitative descriptive manner. Factors that cause the implementation of human rights in the economic field have not been fully realized because between legal policies and legal implementation have not been running consistently and simultaneously. The realization of human rights in the economic field is still only limited to issues and has not become a concrete implementation. The role of the Government in the prevention and overcoming of trafficking in women is still limited to political will by the issuance of a law that ratifies the ASEAN Convention Against Trafficking in Persons, Especially Women and Children, then followed by Institutional Infrastructure Compilation. The role of Educational Institutions and Non-Governmental Organizations in the prevention and prevention of trafficking in women, has responded with action, prevention and handling of trafficking in women, through the socio-economic empowerment of families and advocacy in handling cases of trafficking in women. The struggle and movement for the achievement of feminism justice, in the economic field is carried out by empowering the family economy, improving education and expanding access to job search for women by utilizing information technology.